Factors Associated with the Incidence of Premature Rupture of Membranes - Shofia Nur Lathifa; Faizah Betty Rahayuningsih (Indonesian Journal of Global Health Research, 2025)
Premature Rupture of Membranes (PROM) is a significant obstetric problem, characterised by rupture of the amniotic membrane before delivery, which has the potential to cause complications in maternal and infant health. Analyse the factors associated with the incidence of PROM in RSUD dr. Moewardi, Surakarta. This study used an analytic observational design with a cross-sectional approach. Inclusion criteria were medical records of pregnant women in September 2023 - August 2024. Exclusion criteria in the study were incomplete medical record data of pregnant women. A total of 200 medical records were divided into groups of 100 with PROM status and 100 with non-PROM status. Statistical analyses were performed using univariate and bivariate methods, including the chi-square test to determine significant associations. Factors that had a significant association with PROM included patient referral status (p=0.042), gestational age (p=0.014), parity (p=0.017), history of infection (p=0.001), and chronic diseases (p=0.024). Factors such as maternal age, education, occupation, marital status, and history of abortion showed no significant association with PROM. The incidence of PROM is influenced by certain factors related to the mother's condition and pregnancy, so prevention and early intervention strategies are needed for at-risk populations.